APLIKASI PENYEDERHANAAN CONTEXT FREE GRAMMAR - Rico Andrian; Wamiliana .; Andriyan Hutomo (Jurnal Komputasi, 2015)
This research is done by making an application to simplify Context Free Grammar (CFG). The process of making the application starts from designing the algorithm using eXtreme Programming method as system development methods until get the application to simplify Context Free Grammar (CFG). The testing method to test the application is Black Box Testing. The result shows that the application can simplify Context Free Grammar smoothly, and how to simplify Context Free Grammar step by step. Context Free Grammar (CFG) simplification has  three stages, eliminating espsilon production, eliminating unit production and eliminating useless production, those three stages must be done sequentially. Keywords: Chomsky Normal Form, Context Free Grammar, Greibach Normal Form, Prototype Method